A Comparative Study of Traditional vs. ChatGPT-Assisted Pronunciation Teaching in Vocational Universities - Liao, Liling; Lin, Ziyue (Forum for Linguistic Studies, 2025)
Pronunciation teaching (PT) is crucial for improving oral communication, particularly in vocational universities where students require practical language proficiency for professional purposes. With advancements in artificial intelligence (AI), integrating tools like ChatGPT into language instruction offers new opportunities to enhance pronunciation development. This study examines the effectiveness of ChatGPT-assisted pronunciation instruction compared to traditional classroom-based methods in vocational university settings. A total of 114 non-English major students were randomly divided into two groups. Group A (GA) received traditional teacher-led pronunciation instruction, while Group B (GB) practiced with ChatGPT through conversational dialogues, AI-generated feedback, and pronunciation tasks. Over six weeks, both groups completed pre- and post-tests using a structured rubric assessing clarity, intonation, and segmental precision. Data were analyzed using paired and independent samples t-tests and ANOVA via IBM SPSS 29. Results showed that the ChatGPT-assisted group achieved significantly greater improvements in clarity and accuracy (p < 0.001) than the traditional group. These findings indicate that AI-assisted instruction provides effective personalized feedback, enhances engagement, and accelerates pronunciation learning. The study concludes that integrating ChatGPT-based approaches can serve as a valuable supplement to traditional pronunciation teaching, promoting more efficient and interactive language learning in vocational education.